Analisis Kepuasan Pelanggan Jasa Pengiriman Barang Di J&T Cargo Cabang Sarimanah Kota Bandung - Indra Batara Siahaan; Nurlaela Kumala Dewi; Syafrianita Syafrianita (Journal of Innovative and Creativity, 2025)
A Customer satisfaction in delivery services is important. Customer satisfaction is obtained from the quality of service offered by the delivery service. J&T Cargo Sarimanah Branch is a delivery service that offers quality service to customers so that customers have satisfaction when using the service. In this study, J&T Cargo Sarimanah Branch became a research to see whether the quality of service on customer satisfaction. Research on service quality has a significant effect on customer satisfaction and looks at the variables that are prioritized in meeting customer satisfaction, this study uses the servqual method (service quality) to measure the extent to which the quality of service provided by J&T Cargo Sarimanah Branch and the IPA method (Importance Performance Analysis) to determine the priorities of variables that must be maintained and improved again. The results of this study show a positive value on 18 variables that have been tested and show a value of 2.99. Where the average score shows customer satisfaction with the quality of service J&T Cargo Sarimanah Branch exceeds customer expectations (high satisfaction).